Heat shock protein 27 phosphorylation state is associated with cancer progression - Katsogiannou, Maria; Andrieu, Claudia; Rocchi, Palma (Frontiers in Genetics, 2014)
Understanding the mechanisms that control stress-induced survival is critical to explain how tumors frequently resist to treatment and to improve current anti-cancer therapies. Cancer cells are able to cope with stress and escape drug toxicity by regulating heat shock proteins (Hsps) expression and function. Hsp27 (HSPB1), a member of the small Hsp family, represents one of the key players of many signaling pathways contributing to tumorigenicity, treatment resistance, and apoptosis inhibition. Hsp27 is overexpressed in many types of cancer and its functions are regulated by post-translational modifications, such as phosphorylation. Protein phosphorylation is the most widespread signaling mechanism in eukaryotic cells, and it is involved in all fundamental cellular processes. Aberrant phosphorylation of Hsp27 has been associated with cancer but the molecular mechanisms by which it is implicated in cancer development and progression remain undefined. This mini-review focuses on the role of phosphorylation in Hsp27 functions in cancer cells and its potential usefulness as therapeutic target in cancer.